Leptin Elicits In Vivo Eosinophil Migration and Activation: Key Role of Mast Cell-Derived PGD2 - Amorim, Natália R. T.; Souza-Almeida, Glaucia; Luna-Gomes, Tatiana; Bozza, Patricia T.; Canetti, Claudio; Diaz, Bruno L.; Maya-Monteiro, Clarissa M.; Bandeira-Melo, Christianne (Frontiers in Endocrinology, 2020)
Eosinophil are key regulators of adipose tissue homeostasis, thus characterization of adipose tissue-related molecular factors capable of regulating eosinophil activity is of great interest. Leptin is known to directly activate eosinophils in vitro, but leptin ability of inducing in vivo eosinophilic inflammatory response remains elusive. Here, we show that leptin elicits eosinophil influx as well as its activation, characterized by increased lipid body biogenesis and LTC4 synthesis. Such leptin-triggered eosinophilic inflammatory response was shown to be dependent on activation of the mTOR signaling pathway, since it was (i) inhibited by rapamycin pre-treatment and (ii) reduced in PI3K-deficient mice. Local infiltration of activated eosinophils within leptin-driven inflammatory site was preceded by increased levels of classical mast cells-derived molecules, including TNFα, CCL5 (RANTES) and PGD2. Thus, mice were pre-treated with a mast cells degranulation agent compound 48/80 which was capable to impair leptin-induced eosinophil recruitment and activation. In agreement with an indirect mast cell-driven phenomenon, eosinophil accumulation induced by leptin was abolished in TNFR-1 deficient and also in HQL-79-pretreated mice, but not in mice pretreated with neutralizing antibodies against CCL5, indicating that both typical mast cell-driven signals TNFα and PGD2, but not CCL5, contribute to leptin-induced eosinophil influx. Distinctly, leptin-induced eosinophil lipid body (lipid droplet) assembly and LTC4 synthesis appears to depend on both PGD2 and CCL5, since both HQL-79 and anti-CCL5 treatments were able to inhibit these eosinophil activation markers. Altogether, our data show that leptin triggers eosinophilic inflammation in vivo via an indirect mechanism dependent on activation of resident mast cell secretory activity and mediation by TNFα, CCL5 and specially PGD2.